Empowering Community via Composting Practices in Promoting Sustainable Lifestyle - Ridzuan, Mohd Ridzlie; Abas, Muhamad Azahar; Kadir, Siti Mariam Abdul; Sibly, Suzyrman; Nor, Norizan Md (Thammasat University, 2012)
Composting practice is among the many sustainable practices that can be easily carried out through either small or large scale efforts. Unfortunately, composting has not been widely practiced by the public due to lack of awareness. This paper is part of a research project to promote and diffuse sustainable lifestyle to the community by exploring how the sustainability agenda can be partly addressed through composting practices carried out within the Universiti Sains Malaysia, Penang campus to its surrounding neighborhood. The project highlights the university community engagement to achieve community empowerment with regard to sustainable urban lifestyle. The result indicates a need to increase community awareness with regards to composting practices in order to inculcate sustainable lifestyle. The university community can be regarded as the agents to diffuse and transfer knowledge on composting best practices.